Quality of life in work (qol): the workers conception - Marcondes de Salles, Paulo Eduardo; Federighi, Waldomiro José (O Mundo da Saúde, 2006)
The present study aims at a first moment to present a description of the conceptual evolution of work and its relation to questions of contract, work opportunities and quality of life in the work environment. This is followed by a report on workers under- standing of quality of life. This required initially a bibliographic survey and later the construction of an appropriate instrument that was applied to the research’s 412 participants. The results present data related to the following investigated dimensions: compensation, social integration, work conditions, working hours and displacements, services programming, use and development of capacities, the individual and its role in the company and the company. One concludes that quality of life in work is perceived individually by the employees, and that aspects linked to it involve security conditions in the workplace, remuneration, benefits, chances of growth and learning, promotions and a positive climate and social justice, among others.